Industrial policy and the clothing and textile industry in South Africa - Molekwa, Ben Thayi (My University, 2018)
South Africa has had a wide range of industrial policy interventions with varied results. Many firms in the clothing and textile industry are closing down while many of those remaining continue to perform poorly in terms of production and employment. The purpose of the study is to investigate whether clothing and textile firms in South Africa are globally competitive, examine and explain why industrial policy measures have not generated expected results and reflect on possible recommendations for industrial policy measures that will make the clothing and textile industry globally competitive. The researcher examined the past and current industrial policy measures using the qualitative research method and collected data through interviews with employers, employees, the Industrial Development Corporation as the implementing agency, the Textile Federation as an important stakeholder, government policy makers, and the workers’ representative body, namely the South African Clothing and Textiles Workers’ Union. The findings revealed that the clothing and textile industry is not competitive because of relatively high wages and salaries, lack of up-to-date technology in the industry, and low productivity and pay ratio. The analysis of industrial policy documents, supported by a study on clusters, suggests that there are industrial deficiencies in South Africa’s manufacturing industry due to uncoordinated clusters. A cluster, in this context, refers to a group of similar firms sharing resources and best practices aimed at reducing production costs. In contributing to existing knowledge, the study makes use of four theories that recognise the four factors of production (labour, capital, land, and entrepreneurship) as important elements of industrial policy and competitiveness. These theories are absolute advantage, comparative advantage, the Heckscher-Ohlin theory, and Porter’s Diamond Framework of Competitiveness. Implicit in these theories is that to achieve competitiveness, the price of production factors must be kept to a minimum. The theories assume that the competitiveness of economies flows from the traditional factors of production, particularly capital and labour; and that capital investment, the division of labour (labour specialisation) and free trade are the engines of growth. The main shortcomings inherent in these theories are that, firstly, they advocate for as little government interference in the economic system as possible, or a policy of laissez-faire. Secondly, the theories tackle the same problem by providing models that clarify competitiveness of international trade based on differences in productivity levels between countries, without explaining why these differences exist. South Africa can learn lessons from the East Asian economies’ use of the Dynamic Capacity Development Methodology of Policy Formulation, especially the roles played by the Framework and Ingredients approaches that give guidance on how to intervene in the economy and what areas are relevant for interventions that lead to industrialisation and competitiveness. A ‘Coordination System’ identifies the role-players in the economy as state, firms and the market. This study recommends three industrial policy measures: encouraging exports of manufactured goods; encouraging technology; and promoting education. These measures should be part of discussions during Cluster activities. Furthermore, the study recommends the introduction of the Adopt-a-Cluster model through which government trains officials to implement industrial policies and actively participate in the activities of clusters which, according to Industrial Policy documents, are not properly coordinated. The study proposes further research into why firm owners are not keen to borrow capital and buy modern capital equipment.
A thesis submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in fulfillment of the requirements for the degree of Doctor of Philosophy March 2018